Critique de la modernité Modernité de la critique (Altre Modernità, 2010)
Criticism, as intellectual posture in analysing reality, is tightly joined to Modernity, no matter how problematic such a link could often be. As a matter of fact, if criticism has led to modern society through the Enlightenment, its errors or deceptions often cause the coming back to irrationality and individualism. Moreover ambiguity results from criticism itself, even in its greatest achievements as tolerance and freedom. Granted to our selves, these principles are less evident when others' opinions or beliefs are involved. On the other hand, criticism may cause a nihilistic meaninglessness in a postmodern society risking to disunite itself. But criticism and rhetoric reason could be the instruments of a renewed collective will whose aim would be the comprehension of reality through a pragmatic and experimental knowledge and without any prejudice. This is the task of a postmodern practice of collective discussion.
Keywords: praxis critique; épistémologie de la critique; coupure cognitive; lieux commun; mythe moderne; raison rhétorique